Rinovírus humano em infecções respiratórias agudas em crianças menores de cinco anos de idade: fatores envolvidos no agravamento da doença - Costa, Lourenço Faria (2012)
Although human rhinoviruses (HRV) have been shown to cause common cold, they are increasingly found in severe respiratory infections. Whether or not disease severity may be increased by the presence of a second virus or comorbidities was investigated, such as the HRV frequency. By using IFA and/or RT-PCR we tested 434 nasopharyngeal aspirates from children less than five years old presenting acute respiratory disease for presence of HRV, respiratory syncytial virus (RSV), influenza virus, parainfluenza virus, adenovirus and human metapneumovirus. HRV was characterized through VP4 genome analysis. Thus, at least one virus was detected in 384 samples and HRV was detected in 181 (41.7%) samples: in 107 as the single agent and in 74 with another virus. Moderate-to-severe cases rose significantly in co-infections (p=0.0070). However, RSV, which causes severe disease, was found in 32 co-infections. By removing these cases, moderate-to-severe cases in co-infections reduced to 35.7% (15/42), which is similar to the frequency found in single infections. Similar results was observed according to symptoms, in which URT involvement predominated in HRV single infections. Nevertheless, HRV was responsible for a considerable number of bronchiolitis and wheezing symptoms. Presence of comorbidities, specially early age, prematurity and congenital heart diseases, in single infections rose from 46.6% (34/73) in mild cases to 79.4% (27/34) in moderate-to-severe cases (p=0.0014). From 42 characterized HRV species, HRV-A and HRV-C presented similar proportions (21 and 19, respectively) with no difference of clinical severity. Two enterovirus, poliovirus and echovirus, were also identified. Despite HRV was related mostly with mild symptoms, our results showed that HRV were a very frequent respiratory agent found in many moderate-to-severe cases. The presence of another virus, except for RSV, may not be associated with increased disease severity, which may rather be caused by presence of comorbidities and by the HRV infection itself. We also did not found relation of increasing disease severity according to specie. Finally, we call attention for the possibility of enterovirus detection in RT-PCR HRV investigation, emphasizing the importance of molecular characterization of HRV. Further efforts must be done in attempt to include breast feeding and atopic diseases in parents to accurately evaluate other risk factors of developing severe respiratory disease by HRV infections, and include more samples in the molecular characterization of these agents.